2002
DOI: 10.1002/erv.476
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐morbid psychiatric morbidity, comorbidity and personality in patients with anorexia nervosa compared to their healthy sisters

Abstract: Anorexia nervosa (AN) has been linked with pre-morbid disorders, comorbidity, and specific personality traits in between-family case-control studies. However, these findings have not been replicated in within-family studies, and it is not known whether these factors are linked specifically with AN or are shared familial factors. We aimed to compare pre-morbid disorders, comorbidity, and specific personality traits between sister-pairs discordant for AN. Forty-five families with two sisters discordant for AN we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 35 publications
2
27
2
Order By: Relevance
“…In line with prior studies of childhood OCPTs in women with EDs (Anderluh et al, 2003;Gillberg, Rastam, & Gillberg, 1995;Karwautz, Rabe-Hesketh, Collier, & Treasure, 2002), our hypotheses were that participants with a history of an ED would report a greater endorsement of behaviours associated with OCPTs in childhood than a sample of non-clinical control participants and that these traits would be apparent to informants.…”
Section: Introductionmentioning
confidence: 81%
“…In line with prior studies of childhood OCPTs in women with EDs (Anderluh et al, 2003;Gillberg, Rastam, & Gillberg, 1995;Karwautz, Rabe-Hesketh, Collier, & Treasure, 2002), our hypotheses were that participants with a history of an ED would report a greater endorsement of behaviours associated with OCPTs in childhood than a sample of non-clinical control participants and that these traits would be apparent to informants.…”
Section: Introductionmentioning
confidence: 81%
“…Moreover, lifetime diagnoses of depression in individuals with AN have been as high as 80% (Ivarsson et al, 2000). Despite discrepant findings, research has found depression to predate the onset of AN (Iwasaki et al, 2000;Karwautz et al, 2002).…”
Section: Negative Mood and Anxietymentioning
confidence: 93%
“…Further evidence of abnormalities in AN in the feeling timescale is suggested by the high rates of comborbid anxiety and mood disorders in AN, relative to the general population (Braun, Sunday, & Halmi, 1994;Geist, Davis, & Heinman, 1998;Godart, Flament, Lecrubier, & Jeammet, 2000;Ivarsson, Rastam, Wentz, Gillberg, & Gillberg, 2000;Iwasaki, Matsunaga, Kiriike, Tanaka, & Matsui, 2000;Karwautz, Rabe-Hesketh, Collier, & Treasure, 2002;Kaye, Bulik, Thornton, Barbarich, & Masters, 2004;Thornton & Russell, 1997). Rates of anxiety disorders have been as high as 83% with particularly high rates of obsessive compulsive disorder (OCD) (Godart et al, 2000).…”
Section: Negative Mood and Anxietymentioning
confidence: 97%
See 1 more Smart Citation
“…The median age at the onset of the eating disorder was 16 (14)(15)(16)(17)(18) years. The median duration of the eating disorder was 63 (36-108) months.…”
Section: Resultsmentioning
confidence: 99%